(untitled) (Jurnal Bahasa, 2005)
Many Malay grammarians, namely Asmah (1993), Nik Safiah et al. (1997), Hashim Musa (1993), Liaw Yock Fang and Abdullah Hassan (1994), and Za’ba (2000) have discussed about reduplication and their focus primarily on the morphological aspect. There are only a few studies that explore meanings of the reduplicated forms. Nor Hashimah (2002) suggests that based on semantics perspective, Malay redupli-cation conveys specific and non-specific meanings. Numerical cardinals and quantifiers are also regarded as part of reduplication. The phrase `tiga ekor ayam’ (three hens) is in plural forms - the numeral `tiga’ marks the plurality and the nominal ’ayam’ is not reduplicated. Malay grammarians propose the same rule for quantifiers. The phrase ‘semua guru’ (all teachers) is already in plural form and therefore the word ’guru’ does not need to be reduplicated. Nevertheless, the writ-ten and spoken data prove otherwise. The analysis on functions of numerical reduplications will be more exiting if corpus with big data is examined. Accordingly, semantic analysis of bridging cross-refer-ence and reference assignment explains the di, fferences between the two numerical reduplications adequately.